The Influence of Web Design, Ease of Use, and Security on BNI Mobile Banking Customer Satisfaction - Jestin Erlangga; Audita Nuvriasari (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of web design, ease of use, and security on BNI mobile banking user satisfaction. The population in this study are BNI bank customers who actively use BNI mobile banking services and BNI customers who live in the Yogyakarta area, using purposive sampling. This study uses 100 samples. The data collection technique used was a survey method with the research instrument used being a questionnaire with a Likert scale. The results of this research analysis show that: (1) web design has a positive and significant effect on customer satisfaction, (2) ease of use has a positive and significant effect on customer satisfaction, and (3) security has a positive and significant effect on customer satisfaction.